Numerical Simulation Research on Cutting Rock with a PDC Cutter Assisted by an Impact Force - Yong Wang; Hongjian Ni; Ruihe Wang; Bin Huang; Shubin Liu; Heng Zhang (Advances in Civil Engineering)
Extensive studies have been carried out on cutting rock with a PDC cutter, but cutting rock assisted by impact force is rarely studied. In this paper, cutting rock using conical and cylindrical PDC cutters assisted by impact force were researched with the explicit dynamic model. The laws of cutting rock using a cylindrical cutter assisted by impact force are the same as those of a conical cutter. There are thresholds of impact frequency and amplitude when they are single variables. When impact frequency is lower than the threshold frequency, the impact frequency is the dominant frequency in the frequency spectrum of weight on bit (WOB), and the amplitude of dominant frequency and removal volume decreases with the increase of impact frequency. When the impact frequency is higher than the threshold frequency, there is no dominant frequency in the frequency spectrum of WOB, and the removal volume behaves the same. When the impact force is lower than the threshold amplitude, there is no dominant frequency in the frequency spectrum of WOB, and it does not affect the removal volume but the removal volume is positively correlated with the impact amplitude. When the impact amplitude is higher than the threshold amplitude, the removal volume is also positively correlated with the impact amplitude, and the removal volume assisted by low-frequency (20 Hz and 40 Hz) impact force is higher. The frequency threshold and amplitude threshold of the conical cutter are smaller than those of the cylindrical cutter. Although the cutting depth and removal volume of the conical cutter are lower than those of the cylindrical cutter, the amplifications of cutting depth and removal volume of the conical cutter are higher than those of the cylindrical cutter when assisted by impact force.